2019
DOI: 10.1002/ece3.5494
|View full text |Cite
|
Sign up to set email alerts
|

Moderate grazing promotes the root biomass in Kobresia meadow on the northern Qinghai–Tibet Plateau

Abstract: Grazing is an important modulator of both plant productivity and biodiversity in grassland community, yet how to determine a suitable grazing intensity in alpine grassland is still controversy. Here, we explore the effects of different grazing intensities on plant biomass and species composition, both at community level and functional group level, and examines the productivity–species richness relationship under four grazing patterns: no grazing (CK), light grazing (LG), moderate grazing, (MG) and heavy grazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 54 publications
(70 reference statements)
5
15
1
Order By: Relevance
“…Breaking down the results by management regime, rhizome biomass was strongly and disproportionally (in relation to aboveground biomass) affected by high intensity. We suggest that this disparity is generated by the use of stored resources for regrowth after damage (Klimeš and Klimešová 2002, Dai et al 2019) and by top‐down control constraining plant capacity to acquire new resources (Iwasa and Kubo 1997, Wigley et al 2020). Lower biomass allocation belowground into rhizomes may decrease the capability of temperate grassland plants to store resources and carbon below the soil surface (Zhou et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Breaking down the results by management regime, rhizome biomass was strongly and disproportionally (in relation to aboveground biomass) affected by high intensity. We suggest that this disparity is generated by the use of stored resources for regrowth after damage (Klimeš and Klimešová 2002, Dai et al 2019) and by top‐down control constraining plant capacity to acquire new resources (Iwasa and Kubo 1997, Wigley et al 2020). Lower biomass allocation belowground into rhizomes may decrease the capability of temperate grassland plants to store resources and carbon below the soil surface (Zhou et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Alpine and subalpine grasslands suffer from reduced nutrient availability and harsh environmental conditions, and plants growing in these habitats presumably develop adaptive coping strategies (Chapagain et al, 2019). Disturbance regimes, such as harvesting, grazing, trampling, and fire, also play influential positive (Chen et al, 2014;Dai et al, 2019) or negative (Chapagain et al, 2019;Kreziou et al, 2015) roles in determining the growth and persistence of plants and could be important elements of an optimal grassland management strategy for alpine meadows.…”
mentioning
confidence: 99%
“…Previous studies have shown that herbivores induce underground effects by changing the composition of vegetation and have an ecosystem‐specific impact on soil nematode communities (Andriuzzi & Wall, 2017; Bardgett & Wardle, 2003; Wang et al, 2018). Moderate grazing disturbance can promote soil fertility (Li et al, 2019), maximize aboveground biodiversity (Dai et al, 2019; Pulungan et al, 2019; Souther et al, 2020; Yan et al, 2020), and significantly increase underground biomass and diversity (Dai et al, 2019; Liu et al, 2021; López‐Mársico et al, 2015; Wu et al, 2014). There may be two reasons for the discrepancy between the findings of these studies and our research results.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to grazing exclusion, light grazing results in a high soil carbon–nitrogen ratio, whereas the carbon–nitrogen ratio associated with heavy grazing is low (He et al, 2019; Zhang et al, 2017; Zhou et al, 2017). Additionally, the belowground biomass of plants changes in response to grazing intensity and shows a substantial increase with moderate grazing (Dai et al, 2019; Liu et al, 2021; López‐Mársico et al, 2015; Wu et al, 2014). Furthermore, moderate grazing disturbance promotes soil fertility (Li et al, 2019) and increases aboveground biodiversity (Pulungan et al, 2019; Souther et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation